2004
DOI: 10.1080/03014460410001723996
|View full text |Cite
|
Sign up to set email alerts
|

Can greater muscularity in larger individuals resolve the 3/4 power-law controversy when modelling maximum oxygen uptake?

Abstract: Summary. Background: The power function relationship, MR ¼ aÁm b , between metabolic rate (MR) and body mass m has been the source of much controversy amongst biologists for many years. Various studies have reported mass exponents (b) greater than the anticipated 'surface-area' exponent 0.67, often closer to 0.75 originally identified by Kleiber. Aim: The study aimed to provide a biological explanation for these 'inflated' exponents when modelling maximum oxygen uptake ( _ V VO 2 max), based on the observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
(17 reference statements)
3
24
0
Order By: Relevance
“…The ANCOVA analyses reported by Nevill et al (2004a) not only confirmed that the power function relationship between VO 2 max and body mass alone resulted in an \inflated" mass exponent of 0.75 (although we acknowledge that the 95% confidence interval, from 0.56-0.93, does encompass the surface-area law exponent of 0.67), but also confirmed that the larger soccer players had disproportionately greater leg muscle girths. When the analysis was repeated incorporating calf and thigh muscle girths together with stature (rather than body mass) as predictor variables, the analysis not only explained significantly more of the variance in VO 2 max compared with body mass alone (using the adjusted R 2 to account for the different number of fitted parameters), but the sum of the exponents confirmed a surface-area law.…”
Section: Caution When Fitting and Interpreting Allometric Power Functmentioning
confidence: 55%
See 2 more Smart Citations
“…The ANCOVA analyses reported by Nevill et al (2004a) not only confirmed that the power function relationship between VO 2 max and body mass alone resulted in an \inflated" mass exponent of 0.75 (although we acknowledge that the 95% confidence interval, from 0.56-0.93, does encompass the surface-area law exponent of 0.67), but also confirmed that the larger soccer players had disproportionately greater leg muscle girths. When the analysis was repeated incorporating calf and thigh muscle girths together with stature (rather than body mass) as predictor variables, the analysis not only explained significantly more of the variance in VO 2 max compared with body mass alone (using the adjusted R 2 to account for the different number of fitted parameters), but the sum of the exponents confirmed a surface-area law.…”
Section: Caution When Fitting and Interpreting Allometric Power Functmentioning
confidence: 55%
“…The new methodology of adopting and combining muscle girths and stature measurements as covariates (Nevill et al, 2004a) has some similarities to the approach proposed by Darveau et al (2002). Darveau et al (2002) advocated combining a weighted sum of mass exponents, each estimated from a diverse range of control sites or processes known to contribute to metabolic pathways.…”
Section: Caution When Fitting and Interpreting Allometric Power Functmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the active muscle mass during exercise may be an even more appropriate variable to normalize VO 2max 13 . Similarly, other studies have used MV to normalize VO 2max , since MV better represents the active muscle mass during exercise 8,11,12 . Welsman et al 11 found that VO 2max and power were higher among boys compared to girls using body mass, whereas no significant difference was found between sexes when data were normalized by MV using either ratio or allometric scaling.…”
Section: Discussion Topicsmentioning
confidence: 99%
“…Some studies have used muscle volume (MV), free fat mass (FFM), total muscle mass or lower limb muscle mass as normalizing variables in the attempt to adjust for differences in body dimensions 6,8,11,12 . These variables were chosen to reflect the reality that under maximal intensity exercise, 90% of blood flow and VO 2 are allocated to ATP synthesis during muscle contraction.…”
Section: Discussion Topicsmentioning
confidence: 99%